The Author’s Method of Expression (Texas Journal of Philology, Culture and History, 2023)
In this article, the role of fiction in raising a language to the level of a literary language is discussed. The services of the author of the work were discussed in opening up the rich possibilities of the literary language. Scientific sources on the subject were analyzed